Structural and Functional Characteristics of the B-domain-deleted Recombinant Factor VIII Protein, r-VIII SQ - Sandberg, Helena; Almstedt, Annelie; Brandt, Jörgen; Gray, Eva; Holmquist, Leif; Oswaldsson, Ulla; Sebring, Stefan; Mikaelsson, Marianne (Thrombosis and Haemostasis, 2001)
Recombinant factor VIII SQ (r-VIII SQ), ReFacto®, is a recombinant factor VIII product similar to the smallest active factor VIII protein found in plasma-derived factor VIII (p-VIII) concentrates. The protein comprises two polypeptide chains of 80 and 90 kDa and lacks the major part of the heavily glycosylated B-domain i.e. amino acids Gln744 to Ser1637. r-VIII SQ retains six potential glycosylation sites for N-linked oligosaccharides at asparagine residues 41, 239, 582, 1685, 1810 and 2118.We describe a thorough comparison of the characteristics of r-VIII SQ with those of p-VIII. The primary and secondary structures of r-VIII SQ were in good agreement with that of B-domain-deleted p-VIII (p-VIII-LMW) as shown by SDS-PAGE, Western blotting with antifactor VIII antibodies, tryptic mapping, amino acid sequence analysis and circular dichroism spectroscopy. A few divergences also existed. Thus r-VIII SQ was shown to contain a small amount of the single chain primary translation product of 170 kDa and also the product specific sequence of 14 amino acids, the SQ-link, in the C-terminal end of the 90 kDa chain. It was shown that r-VIII SQ had a high specific activity of about 14,000 IU VIII:C/mg as determined by use of a chromogenic substrate assay. The r-VIII SQ protein was comparable to p-VIII forms with a retained B-domain, in terms of potency measured by a chromogenic substrate or a two-stage clotting assay, in interactions with thrombin, and with activated protein C (APC) in combination with Protein S. The ability of r-VIII SQ to participate as a cofactor in factor Xa generation in a mixture of factors IXa and X, phospholipid and calcium was in conformity with that of p-VIII. Furthermore r-VIII SQ had a good binding capacity for phospholipid vesicles and von Willebrand factor (vWF) as shown in gel filtration studies. The same kinetics in binding to von Willebrand factor was found for r-VIII SQ and p-VIII as determined by real-time biospecific interaction analysis (BIA) with use of the BIAcore® instrument. The apparent association rate constant was 4 × 106 M−1s−1. Two dissociation rate constants were found, 1 × 10−2s−1 and 4 × 10−4s−1. The results extend the present knowledge that the factor VIII B-domain is dispensable for the factor VIII cofactor function in hemostasis.
Keywords: Recombinant; factor VIII; B-domain-deletion; structure; function